Pengenalan Sejarah Lokal Kalimantan Tengah melalui Pemanfaatan Museum Balanga sebagai Sumber Belajar bagi Siswa Kelas X E MAN Kota Palangka Raya. - Niqma Salsabila; Suryanti Suryanti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Introduction of local history of Central Kalimantan through the utilization of the Balanga Museum as a learning resource for Grade X E students of MAN Kota Palangka Raya aims to describe the implementation of museum-based learning activities and analyze their contribution to students’ understanding of local history. This study uses a descriptive qualitative approach within community service activities (PKM) through field trip methods. Data were collected through participatory observation, documentation, and interactive discussions during learning activities at the Balanga Museum. The results show that museum-based learning enhances students’ engagement, provides meaningful learning experiences, and improves their understanding of local history. Learning outside the classroom through direct observation of historical objects makes students more active and interested in learning history. These findings indicate that museums can function as effective contextual learning resources in supporting history education, especially in introducing local cultural heritage to students.